Implementation and Effectiveness of Antiretroviral Therapy in Greenland - Lohse, Nicolai; Ladefoged, Karin; Obel, Niels
Analyses from the Danish HIV Cohort Study showed that, despite comparable economic means and general education of healthcare personnel, antiretroviral treatment of HIV in Greenland began later and has been implemented at a slower pace with lower therapeutic effectiveness than in Denmark. However, implementation and quality of care improved considerably in recent years.